Critical success factors for the receptiveness of Islamic home financing in Malaysia - Hanudin Amin (2020)
Purpose – The purpose of this study is to examine the critical success factors (CSFs) for the receptiveness of Islamic home financing in Malaysia. Design/methodology/approach – A framework of the CSFs for the receptiveness of Islamic home financing is developed. The framework evaluates the effects of product type, competitive value proposition, Islamic debt collection policy, Islamic bankers’ knowledge and maqasid al-Shariah compliance on the receptiveness. Data from 744 usable questionnaires are analysed to confirm the applicability of the framework in Islamic home financing context. Findings – The results suggest that product type, competitive value proposition, Islamic debt collection policy, Islamic bankers’ knowledge and maqasid al-Shariah compliance are significantly related to the receptiveness of Islamic home financing. Research limitations/implications – Two limitations are available for future studies. Firstly, the respondents of this study are limited to Malaysians, signifying further testing of the proposed model across different geographies is required to determine the generalisability of the model. Secondly, the contributions of the proposed framework are confined to a specific area of Islamic banking products. Thus, extending the framework to other banking products or conducting a comparative study between Islamic home financing and its conventional peer can improve its generalisability. Practical implications – The results obtained offer a fresh direction on how to market Islamic home financing products successfully, where the new CSFs are brought into play. Originality/value – This study examines the new proposed CSFs for the receptiveness of Islamic home financing in Malaysia.